Socijalna, poduzetnička i e-inkluzija žena starosti 40+ / Social, Entrepreneurial and E-Inclusion of 40+ Women - Džindo, Adnan (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
Several key issues produce the phenomenon of social inclusion. These include: unemployment, inadequate education, poor housing, and an environment with high crime rates, insufficient care for elderly population, poor health, and numerous cases of family breakdown. Therefore, fight against poverty and social exclusion through promotion of integration in the labor market and social integration for marginalized groups is a support to their active social inclusion into social flows. Employment of marginalized – socially excluded groups and implementation of projects for the development of stimulating environment are extremely important and represent the best approach in their social reaffirmation and fight against all types of discrimination. In this context, the development and implementation of agenda for adult learning, with emphasis on computer literacy and entrepreneurship training of persons in middle adulthood are the most important. Namely, support for these projects will enhance the general employment capacity, and reduce the risk of social exclusion and poverty of marginalized groups. The presented case study shows that the development and implementation of targeted programmes of computer and entrepreneurship training for women of 40+ years of age gave excellent results in empowerment of this marginalized group through improvement of computer, entrepreneurship, and social skills, and creating prerequisites to improve their employment and integration in the labor market.